Capsicum germplasm targeted valorization using physicochemical and phytochemical descriptors - Castaño, Esteban; Vega-Muñoz, Maira A.; Grisales-Vásquez, Nancy Yohana; Loaiza-Loaiza, Oscar A.; Henao-Rojas, Juan Camilo; Montoya, Guillermo (Frontiers in Sustainable Food Systems, 2025)
Capsicum species are widely cultivated yet their full industrial potential remains underexplored due to limited characterization of their physicochemical and phytochemical descriptors. In this study, we comprehensively evaluated 284 Capsicum accessions to address this gap and assess their suitability for industrial applications across food, pharmaceutical, and cosmetic sectors. Key quality descriptors—such as capsaicinoids, soluble solids, carotenoids, color index, pH, and texture—were measured and statistical clustering methods, including principal component analysis and k-means clustering, were employed to group accessions based on these traits. The analysis revealed four distinct genotype groups and identified nine standout genotypes with superior attributes; for instance, some accessions exhibited high capsaicinoid content (up to 6,062 mg/kg), elevated soluble solids (up to 17 °Brix), and remarkable carotenoid levels (up to 39.54 mg/g), meeting critical market demands. These findings provide a robust foundation for targeted breeding strategies and underscore the versatility of Capsicum as a valuable genetic resource for sustainable industrial innovation and conservation.